2021
DOI: 10.1016/j.heliyon.2021.e06935
|View full text |Cite
|
Sign up to set email alerts
|

Slaughter performance and meat quality of Begait breed lambs fattened under different diets

Abstract: This study was conducted to evaluate slaughter performance and meat quality of Begait sheep breed reared under different feeding options. Thirty intact fattening lambs (32.81 AE 2.39 kg) were used in randomized completely block design with three dietary treatments in ten replicates for a 90 day feeding trial. Dietary treatments constituted grass hay fed ad libitum to all treatments plus supplemented with mixed diet of 48% wheat bran, 15% molasses, 35% cotton seed cake, 1% salt and 1% limestone (T1); 43% wheat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The pH 24h was determined by completely embedding the electrode head of a calibrated pH meter into the meat sample (while avoiding fat and fascia) until it reached the center of the meat sample; the electrode was allowed to stand for>5 min to take the reading after it had stabilized ( Devapriya et al, 2021 ). The WBSF was measured using a tenderizer by cutting in the direction perpendicular to the muscle fibers(meat-like size: 2 cm × 1 cm × 1 cm) ( Atsbha, Gebremariam, & Aregawi, 2021 ). The cooked meat percentage, cooking loss and dripping loss were determined with reference to the method of Honikel et al ( Honikel, 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…The pH 24h was determined by completely embedding the electrode head of a calibrated pH meter into the meat sample (while avoiding fat and fascia) until it reached the center of the meat sample; the electrode was allowed to stand for>5 min to take the reading after it had stabilized ( Devapriya et al, 2021 ). The WBSF was measured using a tenderizer by cutting in the direction perpendicular to the muscle fibers(meat-like size: 2 cm × 1 cm × 1 cm) ( Atsbha, Gebremariam, & Aregawi, 2021 ). The cooked meat percentage, cooking loss and dripping loss were determined with reference to the method of Honikel et al ( Honikel, 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…The instrumental colour and quality parameters are presented in Table 2. Khliji et al (2010) and Atsbha et al (2021) stated that 95 % of consumers prefer it when the brightness value of meat is above 44; they also found that consumer desire decreased when the brightness value dropped below 34 and that the meat was then considered "dark meat". Although Hemşin, a breed used in this study, showed lower values than the other breeds based on the instrumental brightness values, it was determined that all of the breeds used in this work had brightness values above the aforementioned threshold.…”
Section: Resultsmentioning
confidence: 99%
“…Slaughter performance, including carcass weight and dressing percentage, directly manifests the growth performance and economic value of animals [ 5 , 15 ]. Differences among treatments in SBW, EBW, HCW, net meat percentage, the ratio of meat to bone, and visceral fat percentage were observed at both stages in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Differences among treatments in SBW, EBW, HCW, net meat percentage, the ratio of meat to bone, and visceral fat percentage were observed at both stages in this study. The lower HCW and other slaughter performance recorded in the AL40 groups reflected that restricted feed consumption reduced muscle growth and fat deposition [ 15 , 30 ]. In this study, the body composition of goats undergoes substantial changes with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation